Clinical use of the Insight Inventory in cerebral visual impairment and the effectiveness of tailored habilitational strategies. (8th August 2020) - Tsirka, Asimina; Liasis, Alki; Kuczynski, Adam; Vargha‐Khadem, Faraneh; Kukadia, Roopen; Dutton, Gordon; Bowman, Richard
Abstract : Aim: To investigate the utility of the Insight Inventory (a structured clinical inventory completed by caregivers) for assessment of children with cerebral visual impairment; and to investigate effectiveness of tailored habilitational strategies derived from the responses to the Insight Inventory. Method: Fifty‐one eligible children (26 males, 25 females; mean age 9y 5mo, SD 3y, range 5–16y) were recruited from Great Ormond Street Hospital, London. They underwent baseline assessment including neuro‐ophthalmological and neuropsychological evaluations, and parent‐ and child‐reported ratings on a questionnaire‐based measure of quality of life. Parents also completed the Insight Inventory. On the basis of responses to the Inventory, families received individualized habilitational strategies. Follow‐up assessments 6 months later included repeating the Insight Inventory and quality of life questionnaires. Results: Correlations were found between the Insight Inventory and the Wechsler Intelligence Scale for Children, Fourth Edition, the Beery‐Buktenica Test of Visual‐Motor Integration, and the Benton Facial Recognition Test, suggesting that the Insight Inventory is an effective tool to estimate visual–perceptual difficulties. At 6 months follow‐up, caregiver reports indicated significant improvements in the quality of life of children below the age of 12 years. Interpretation: The Insight Inventory is a simple questionnaire which covers practical aspects of cognitive visual function in everyday life. It provides in‐depth information about the aspects that children struggle with. It can also guide programmes of individualized habilitation strategies, which may enhance the quality of life of younger children. What this paper adds: Questionnaire scores demonstrate biologically plausible correlations with formal neuropsychological tests of visual function. After administration of matched practical habilitational strategies, younger children showed improvement in quality of life and functional vision scores. What this paper adds: Questionnaire scores demonstrate biologically plausible correlations with formal neuropsychological tests of visual function. After administration of matched practical habilitational strategies, younger children showed improvement in quality of life and functional vision scores. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Uso clínico del inventario de visión en discapacidad visual cerebral y la eficacia de estrategias de habilitación personalizadas: Objetivo: Investigar la utilidad del inventario de visión (un inventario clínico estructurado completado por los cuidadores) para la evaluación de niños con discapacidad visual cerebral; e investigar la eficacia de estrategias de habilitación personalizadas derivadas de las respuestas del inventario de visión. Método: Se eligieron 51 niños (26 varones, 25 mujeres; edad media 9 años 5 meses, SD 3 años, rango 5‐16 años) reclutados en el Great Ormond Street Hospital, de Londres. Se sometieron a una evaluación de referencia que incluía evaluaciones neuro‐oftalmológicas y neuropsicológicas. Los padres y los niños realizaron una calificación de la calidad de vida basada en cuestionarios. Los padres también completaron el inventario de visión. Sobre la base de las respuestas al inventario, las familias recibieron estrategias de habilitación individualizadas. Se realizaron evaluaciones de seguimiento a los 6 meses que incluyeron la repetición del inventario de visión y los cuestionarios de calidad de vida. Resultados: Se encontraron correlaciones entre el inventario de visión y la Escala de Inteligencia Wechsler para Niños, Cuarta Edición, la Prueba Beery‐Buktenica de Integración Visual‐Motora y la Prueba de Reconocimiento Facial de Benton, lo que sugiere que el Inventario de visión es una herramienta eficaz para estimar las dificultades visuales‐perceptivas. A los 6 meses de seguimiento, los informes del cuidador indicaron mejoras significativas en la calidad de vida de los niños menores de 12 años. Interpretación: El inventario de visión es un cuestionario sencillo que cubre aspectos prácticos de la función visual cognitiva de la vida cotidiana. Proporciona información detallada. Uso clínico do Inventário Insight em deficiência visual cerebral e a efetividade de estratégias habilitatvas individualizadas: Objetivo: Investigar a utilidade do Inventário Insight (um inventário clínico estruturado completado por cuidadores) para avaliação de crianças com deficiência visual cerebral; e investigar a efetividade de estratégias habilitativas individualizadas derivaram das respostas ao Inventário Insight. Método: Cinquenta e uma crianças elegíveis (26 do sexo masculino, 25 do sexo feminino; média de idade 9a 5m, DP 3a, variação 5‐16a) foram recrutadas o Great Ormond Street Hospital, Londres. Elas passaram por avaliação de linha de base incluindo avaliações neuro‐oftalmológicas e neuropsicológicas, e pontuações reportadas por pais e crianças de uma medida de qualidade de vida em formato de questionário. Os pais também completaram o Inventário Insight. Com base nas respostas do Inventário, as famílias receberam estratégias habilitativas individualizadas. Avaliações de acompanhamento 6 meses depois incluíram repetir o Inventário Insight e questionários de qualidade de vida. Resultados: Correlações foram encontradas entre o Inventário Insight e a Escala Wechsler de Inteligência para Crianças, Quarta Edição, o Teste de Integração visuomotora de Beery‐Buktenica, e o Teste de Reconhecimento Facial, sugerindo que o Inventário Insight é uma ferramenta efetiva para estimar dificuldades visuo‐perceptuais. No acompanhamento de 6 meses, relatos dos cuidadores indicaram melhoras significativas na qualidade de vida de crianças abaixo de 12 anos. Interpretação: O Inventário Insight é um questionário simples que cobre aspectos práticos da funcão visual cognitiva na vida diária. Ele oferece uma informação aprofundada sobre os aspectos com os quais crianças têm dificuldades. Também pode guiar programas de estratégias individualizadas de habilitação, que podem melhorar a qualidade de vida para crianças mais novas.